When the meadow blooms [large type] - Gabhart, Ann H., 1947- (Center Point Large Print, 2022)
"If any place on God's earth was designed to help one heal, it is Meadowland. Surely here, at her brother-in-law's Kentucky farm, Rose and her daughters can recover from the events of the recent past - the loss of her husband during the 1918 influenza epidemic, her struggle with tuberculosis that required a stay at a sanitarium, and her girls' experience in an orphanage during her illness. At Meadowland, hope blooms as their past troubles become rich soil in which their faith can grow. Dirk Meadows may have opened his home to his late brother's widow and her girls, but he keeps his heart tightly closed. The roots of his pain run deep, and the evidence of it is written across his face. Badly scarred by a fire and abandoned by the woman he loved, Dirk fiercely guards his heart from being hurt again. But it may be that his visitors will bring light back into his world and unlock the secret to true healing."--